Identification of Novel Genetic Regulatory Region for Proprotein Convertase FURIN and Interferon Gamma in T Cells - Ortutay, Zsuzsanna; Grönholm, Anna; Laitinen, Melina; Keresztes-Andrei, Melinda; Hermelo, Ismail; Pesu, Marko (Frontiers in Immunology, 2021)
The propoprotein convertase enzyme FURIN promotes the proteolytic maturation of pro-proteins and thereby it serves as an important factor for maintaining cellular homeostasis. In T cells, FURIN is critical for maintaining the T regulatory cell dependent peripheral immune tolerance and intact T helper cell polarization. The enzymatic activity of FURIN is directly associated with its expression levels, but genetic determinants for cell-type specific Furin gene regulation have remained elusive. By exploring the histone acetyltransferase p300 binding patterns in T helper cells, a putative regulatory region at ca. 20kB upstream of Furin gene was identified. When this region was deleted with CRISPR/Cas9 the production of Furin mRNA was significantly reduced in activated mouse T cells. Genome-wide RNA profiling by sequencing revealed that the novel Furin regulator region also impacted the expression of several genes that have previously been associated with the Th1 type hallmark cytokine IFNγ regulation or function. Finally, Furin genetic regulatory region was found to specifically promote the secretion of IFNγ by activated T cells. In sum, our data unravel the presence of Furin expression regulatory region in T cells that has characteristics of a super-enhancer for Th1 cell fate.